The Implication of Caliphate Ideology Movement against the Implementation of Democracy toward Jember Society - Rauf, Moh Abd (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
The internalization of the caliphate ideological movement by several community organizations rolled since the reform era because of the provision public freedom space. One of the organizations that forced to establish the caliphate was Hizbut Tahrir Indonesia (HTI). This paper tries to reveal the ideology concept in the HTI’s perspective and how they internalize the caliphate movement toward the existence democracy in Jember East Java Indonesia. This research uses a type of empirical research with phenomenological approach. The result show that democracy is essentially represent the government and the supreme power of a state. The system of democratic government follows the principle of government from the people, by the people, and for the people. The movement of caliphate was very influential in undermining the value of democracy is known to be very comprehensive. At this time the movement is expanding to various regions, especially in Jember city in changing the general paradigm of society to follow the ideology.